INTERAKSI SOSIAL DALAM NOVEL WUTHERING HEIGHTS KARYA EMILY BRONTE - MUHAMMAD, FADEL; WANTASEN, ISNAWATY L.; PAMANTUNG, RINA P. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACT            This research aims to know the reflections of the types of social interaction in novel Wuthering Heights by Emily Bronte. The writer uses qualitative method, and then describing the result in descriptively. The theories that are used in this research are character analysis by Edgar V. Roberts and social interaction by Georg Simmel. First, the writer identifies character?s dialogues and acts, and then classifying all the data into types of social interaction that Georg Simmel divides into 5 types, which are Exchange, Conflict, Domination, Prostitution and Sociability. There are two questions that the writer forms as the statements of problem of this research, which are 1.) What are types of social interactions that found in novel ?Wuthering Heights? by Emily Bronte? 2.) How the type of social interaction reflected in novel ?Wuthering Heights? by Emily Bronte? Based on the research, the writer just found 4 types of social interaction in this novel, they are Exchange, Conflict, Domination and Sociability. There are no found any data about Prostitution. This data are taken from 3 major characters of this novel. The characters are Heathcliff, as the main character, Cathy, a female character whom Heathcliff falls in love with, and Hindley, a character whom motivates Heathcliff to take revenge. The most social interaction types that these characters used are Conflict and Domination.Keywords: Social Interaction, Georg Simmel, Wuthering Heights, Literature